Relationship between motor competence, weight status, and cardiorespiratory fitness from 7 to 16 years of age - Rodrigues, Luis Paulo (2023)
Strong evidence has been found for a negative relationship between motor competence (MC) and weight status (WS), and a positive one between MC and health related fitness (HRF).